ANALYSIS OF THE EFFECT OF LOCAL TAX AND POPULATION ON LOCAL ORIGINAL REVENUE IN BIREUEN DISTRICT IN 2007-2016 - Risma Yanti; Khairil Anwar (LPPM Universitas Malikussaleh, 2018)
This study aims to Determine the Effect of Local Taxes and the Number of Population on Local Original Revenue in Bireuenn District in 2007-2016. The Data used in this study are secondary Data sourced from Bireuen District Central Bureau of Statistics (BPS) 2007-2016. The method of data analysis used in this study is the Multiple Linear Regression models. The results Showed that the local tax partially has a significant and negative effect on the Local Original Revenue in Bireuen District and the Population has a positive and significant effect on the Local Original Revenue in Bireuen District. Whereas simultaneously the variables of Local Taxes and Population have a positive and significant effect on Original Local Revenue in Bireuen District in 2007-2016.